BERJIWA ENTERPRENEUR UNTUK MERAIH KESUKSESAN DALAM PANDANGAN ISLAM - Munif Efendi (Minhaj: Jurnal Ilmu Syariah, 2020)
Doing all work endeavors solely for seeking the good pleasure of Allah. Implementation of entrepreneurial theory is basically an effort made through self-inherent supervision through creative character innovation to achieve life benefits. Having an entrepreneurial spirit as a correction capital prepares entrepreneurial behavior. Having an entrepreneurial spirit by implementing theory to achieve success includes conclusions of opinion, namely; (1) Intention and belief, having the awareness to do tasks responsibly and trying to complete it, that he is capable. (2) Be aware of abilities, oriented to read opportunities, learn the process of success stages that can be studied. Introspective and does not raise himself with all the abilities to walk according to his busyness. (3) the desire to learn, understand the needs and services to consumers, follow the market in the suitability of new products. (4) Commitment, through stages and evaluations to formulate new strategies, control strategic policies, analyze suitability periodically to make it more effective and minimize risk